Standardization Of The Recipe For Rendang Daging In Nagari Lingkuang Aua Kecamatan Pasaman Kabupaten Pasaman Barat - Shinta Widya Ikrar; Anni Faridah (Jurnal Pendidikan Tata Boga dan Teknologi, 2021)
The quality of beef rendang found in Nagari Lingkuang Aua,Pasaman District,West Pasaman Regency is still diverse,this is because there is no standard recipe for beef rendang in this area,this can be seen in terms of shape,color,aroma,texture and taste.The aim of the research was to obtain standard recipes for beef rendang in this area,so that the standard recipe is useful for preservation to be uniform and preferred.This type of research is a mix of methods combined qualitative and quantitative research.The source of qualitative data obtained 11 informants who are experts in making beef rendang. Sources of quantitative data obtained 10 people who are experts knowing about beef rendang and 5 limited panelists,UNP Catering lecturers.Qualitative data analysis techniques are data reduction,data presentation and conclusions. Quantitative data analysis techniques use the formula (Mx = N ∑/ N).Organoleptic tests on the standard recipe for meat rendang produce a fairly square shape quality,the color of the flesh is dark brown enough,the color of the rendang bran quite blackish brown, fragrant aroma,the texture of the rendang meat is quite soft,the texture of the rendang bran is quite dry,oily,the taste of rendang meat permeates,and the taste of the rendang beef bran is tasty.Keywords: Standardization,Meat Rendang,Lingkuang Aua